The emergence of a change in the prevalence of preeclampsia in a tertiary maternity unit (2004–2016). (18th August 2022) - Horgan, Rebecca; Monteith, Cathy; McSweeney, Lisa; Ritchie, Ruth; Dicker, Patrick; EL-Khuffash, Afif; Malone, Fergal D.; Kent, Etaoin
Abstract: Background: Pre-eclampsia (PET) affects 2–3% of all pregnancies, rising to 5–7% in nulliparous women. This study aimed to investigate the prevalence of PET over a 13-year period. Methods: A retrospective review was performed over a 13-year period (2004–2016) via interrogation of the annual clinical reports of The Rotunda Hospital, Dublin. Results: There was a fall in the overall incidence of PET (nulliparous and multiparous), from a peak of 3.8% in 2007 to 1.5% in 2015. Comparing the first and second halves of the study time-period this decrease was statistically significant ( p < .0001). In nulliparous women, the thirteen-year mean was 4.4% for the study period, with a similar observed reduction from a peak of 5.3% in 2005 to a trough of 2.4% in 2015. Discussion: In our institution, we have shown a decrease in preeclampsia rates over a 13-year period. While the reason for this trend remains unclear, a similar trend has been observed in another tertiary unit and additional research is required to explain the etiology behind these observations.